Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1186/1477-3155-4-14
|View full text |Cite
|
Sign up to set email alerts
|

C60-Fullerenes: detection of intracellular photoluminescence and lack of cytotoxic effects

Abstract: We have developed a new method of application of C60 to cultured cells that does not require water-solubilization techniques. Normal and malignant cells take-up C60 and the inherent photoluminescence of C60 is detected within multiple cell lines. Treatment of cells with up to 200 μg/ml (200 ppm) of C60 does not alter morphology, cytoskeletal organization, cell cycle dynamics nor does it inhibit cell proliferation. Our work shows that pristine C60 is non-toxic to the cells, and suggests that fullerene-based nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 60 publications
2
57
0
Order By: Relevance
“…D ue to its nanom eter size, the pristine C60 fullerenes are able to interact w ith biom ole cules (3,4) an d penetrate th ro u g h the cell m em brane (5,6). They exhibit antioxidant properties (7) and, being non-toxic (at low concentration at least) (8)(9)(10)(11)(12)(13), exert specific health effects (e.g., suppress the grow th o f m alignant tum ors (14,15)). A lthough these molecules have extrem ely low w ater solubility (16), they form stable colloid solutions containing individual C60 fullerenes as well as C60 fullerene aggregates (clusters) in w ater (17,18), w hen subjected to extended m ix ing, sonication, or solvent exchange (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…D ue to its nanom eter size, the pristine C60 fullerenes are able to interact w ith biom ole cules (3,4) an d penetrate th ro u g h the cell m em brane (5,6). They exhibit antioxidant properties (7) and, being non-toxic (at low concentration at least) (8)(9)(10)(11)(12)(13), exert specific health effects (e.g., suppress the grow th o f m alignant tum ors (14,15)). A lthough these molecules have extrem ely low w ater solubility (16), they form stable colloid solutions containing individual C60 fullerenes as well as C60 fullerene aggregates (clusters) in w ater (17,18), w hen subjected to extended m ix ing, sonication, or solvent exchange (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also demonstrated the low cytotoxicity of the hydroxylated Gd 3 N@C 80 (OH) n system in a cell viability study of hen brain and human neuroblastoma SH-SY5Y cells [33]. Overall, these reports demonstrated that fullerenes have low systemic toxicity and ameliorate inflammatory responses due to radical and ROS scavenging properties [22][23][24]29,31,32]. Furthermore, the ease of surface functionalization and ability to use the versatile metallofullerene platform as the basis for multiple imaging agents makes it an ideal candidate for multi-modality imaging applications.…”
Section: Introductionmentioning
confidence: 79%
“…[22][23][24][25]. In regard to the fullerene nanoparticles utilized in this application, the toxicities in vitro and in vivo have been studied extensively [22][23][24][25][26][27][28][29][30][31][32]. Recent studies have also demonstrated the low cytotoxicity of the hydroxylated Gd 3 N@C 80 (OH) n system in a cell viability study of hen brain and human neuroblastoma SH-SY5Y cells [33].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…7 Moreover, the use of liposomes might reduce the reported toxicity of these materials. 8,9 Liposomes have been used widely as drug delivery systems. The main advantages of liposomes as a drug delivery system are the following: (i) they have a very versatile structure that can be easily tailored to bear the properties needed for each specific application, (ii) they can accommodate any type of drug molecules either in their aqueous compartments (hydrophilic drugs) or in their bilayers (lipophilic drugs) or both (ampliplilic drugs), and (iii) they are nontoxic, nonimmunogenic and fully biodegradable.…”
Section: ■ Introductionmentioning
confidence: 99%